2021
DOI: 10.1101/2021.01.07.21249410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Risk of Autopsy-Proven Pneumonia with Sex, Season and Neurodegenerative Disease

Abstract: There has been a markedly renewed interest in factors associated with pneumonia, a leading cause of death worldwide, due to its frequent concurrence with pandemics of influenza and Covid-19 disease. Reported predisposing factors to both bacterial pneumonia and pandemic viral lower respiratory infections are wintertime occurrence, older age, obesity, pre-existing cardiopulmonary conditions and diabetes. Also implicated are age-related neurodegenerative diseases that cause parkinsonism and dementia. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…An important issue is whether or not COVID-19 lower respiratory disease elicits more intense systemic repercussions than typical acute pneumonia. Our investigations ( 112 , 156 , 162 ) indicate that acute or subacute ischemic changes, infarctions or hemorrhages are probably not more common in COVID-19 than they are in subjects dying without COVID-19 or with or without non-COVID-19 acute pneumonia. Early adoption of low molecular weight heparin therapy may have reduced thromboembolism in our study subjects, in comparison with COVID-19 decedents in the first few months of the pandemic.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…An important issue is whether or not COVID-19 lower respiratory disease elicits more intense systemic repercussions than typical acute pneumonia. Our investigations ( 112 , 156 , 162 ) indicate that acute or subacute ischemic changes, infarctions or hemorrhages are probably not more common in COVID-19 than they are in subjects dying without COVID-19 or with or without non-COVID-19 acute pneumonia. Early adoption of low molecular weight heparin therapy may have reduced thromboembolism in our study subjects, in comparison with COVID-19 decedents in the first few months of the pandemic.…”
Section: Discussionmentioning
confidence: 57%
“…Although COVID-19 has reportedly caused disproportionate mortality in those with dementia ( 114 ), and the apolipoprotein E-ε4 allele, a genetic risk factor for Alzheimer AD, may be more common in subjects with severe COVID-19 disease ( 113 , 115–119 ), in the set of subjects that we examined in these studies, there was no apparent predilection of COVID-19 for AD or other major aging-associated neuropathological diagnoses, or an association with the apolipoprotein E-ε4 allele. This may be due to insufficient subject numbers and statistical power, as in a much larger set of AZSAND subjects, we have reported that autopsy-confirmed acute pneumonia is significantly more common in those with concurrent neuropathologically diagnosed major neurodegenerative conditions ( 112 ). It is acknowledged, however, that all of these studies have not considered whether it is specific neurodegenerative processes or just being institutionalized, critically ill and bedbound that is linked to the increased COVID-19 and pneumonia risk.…”
Section: Discussionmentioning
confidence: 90%
“…The finding of an association of dementia with a higher odds of an infectious disease as cause of death, especially of pneumonia is supported by prior literature [ 34 ]. Pneumonia is particularly more common in advanced stages of dementia when dysphagia is present increasing the risk of aspiration pneumonia [ 35 , 36 ]. Our finding that dementia is associated with a lower odds of cancer as cause of death is also consistent with the findings from other studies [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with these conditions are often bedridden and may experience dysphagia, altered mental states, or respiratory muscle weakness, all of which can increase the risk of pneumonia. Additionally, the causes of pneumonia in patients with neurological conditions who also have COPD may be different from those in the general population, which can lead to differences in the distribution of pathogens causing the infection [62].…”
Section: Nervous System Disordersmentioning
confidence: 99%